One-way photoisomerization of ligands for permanent switching of metal complexes - Lvov, Andrei; Mörtel, Max; Heinemann, Frank Wilhelm; Khusniyarov, Marat (Journal of Materials Chemistry C, 2021)
One-way photoisomerization of ligands within metal complexes is an almost unknown phenomenon. We disclosed that a diarylethene-based ligandL-oundergoes quantitative irreversible photoisomerization to a photo- and thermostable annulated isomerL-aboth in a metal-free state and within a spin-crossover iron(ii) complex. The modulation of the electronic structure of the ligand uponL-otoL-aphotoisomerization provides a unique opportunity to change the physical properties, in this case magnetic properties, of the corresponding metal complexes permanently, which is highly attractive for constructing non-volatile permanent memories and components for emerging molecular electronics and spintronics. Importantly, destructive thermal back-switching, which is commonly observed in metal complexes with photochromic ligands, is completely suppressed with our strategy.
CRIS-Team Scopus Importer:2021-04-23